The credit channel in Germany and the UK: Differences in the transmission of monetary policy? - Ulrike Lüdke (Deutsche Bank Research, 2000)
This paper investigates the credit channel in Germany and the United Kingdom. The financial systems of these two countries show substantial structural differences, which leads one to expect that their real sectors respond differently to changes in monetary policy. To the extent that this is the case, the UK's eventual accession to EMU could have non-trivial consequences. However, based on unrestricted VAR models, various interest rate shocks are simulated and it is found that the differences in the transmission effects are relatively small. While the importance of possible identification problems is stressed, the paper hypothesizes that the introduction of a common currency is likely to deepen capital markets and raise competition among credit intermediaries, resulting in a declining dependence on banks in Germany.
Keywords: 330; monetary policy; credit channel; Transmissionsmechanismus; Kreditkanal; Kredit; Kreditmarkt; Geldpolitik; Zins; Elastizität; Schätzung; Vergleich; Deutschland; Großbritannien